PERAN HUMAS DPRD SEBAGAI SUATU SISTEM DAN FASILITATOR PUBLIK (Studi pada DPRD Kabupaten Bima) - Masud masud; Haeril Haeril (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Buton, 2022)
The urgency of this research is to describe the ability of Public Relations as a system and public facilitator for the Bima Regency DPRD in creating accountability and transparency of performance, as well as a positive image during public trust in the Government, especially in the Legislative Institution. This study used descriptive qualitative method. The location of this research is in the Bima Regency DPRD Office. The subjects of this study were selected through purposive sampling technique. The results of the study indicate that the task of Public Relations is a system to establish functional relationships with the public, especially in transforming information (transparency of information and accountability) to the public related to the performance of the DPRD Bima Regency. The leading public relations officer to create, build, improve and maintain the image of the DPRD in public, thereby generating public trust and support for the DPRD's institutional policies. In addition, Public Relations is also present as a public facilitator, to accommodate ideas or aspirations that are found from problems that arise in the community, to be taken into consideration for the implementation of the upcoming DPRD. In this case, all public information is collected later and mapped based on the main problem to be given to the leadership and members of the Bima Regency DPRD in accordance with their duties based on the DPRD's completeness.